1983
DOI: 10.1094/pd-67-1374
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Seeds and Crop Residues as Sources of Inoculum for Pod and Stem Blight of Soybeans

Abstract: for 10 yr, corn rotated with soybeans for 5 ABSTRACT yr, or continuous corn for 10 yr. The Garzonio, D. M., and McGee, D. C. 1983. Comparison of seeds and crop residues as sources of fields were within 11 km of each other. inoculum for pod and stem blight of soybeans. Plant Disease 67:1374-1376. Soil types were all of the Clarion-Nicollet-Webster association. Individual Soybean seed lots of three cultivars (in 1979) and of one cultivar (in 1980) infected with different plots consisted of four 4.8-m rows 0.8 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…According to Garzonio & McGee (1983), the presence of soybean crop residue in the field induced more pod and stem blight infection, mainly on the continuous-soybean. Moreover, several researchers have demonstrated that soybean debris also harbors wheat and maize pathogens such as Fusarium graminearum, Gibberella zeae, Cochliobolus sativus and Leptosphaeria nodorum (Fernandez & Fernandes, 1990;Baird et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…According to Garzonio & McGee (1983), the presence of soybean crop residue in the field induced more pod and stem blight infection, mainly on the continuous-soybean. Moreover, several researchers have demonstrated that soybean debris also harbors wheat and maize pathogens such as Fusarium graminearum, Gibberella zeae, Cochliobolus sativus and Leptosphaeria nodorum (Fernandez & Fernandes, 1990;Baird et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…sensu Kmetz et al (10,21) and P. sojae are the most common Phomopsis anamorphs isolated from soybean plant parts in Ohio (9)(10)(11)(12)21), and the separation of Phomopsis anamorphs from soybean into these two types has been recognized by researchers in other parts of the country (3,19,24,29). sensu Kmetz et al (10,21) and P. sojae are the most common Phomopsis anamorphs isolated from soybean plant parts in Ohio (9)(10)(11)(12)21), and the separation of Phomopsis anamorphs from soybean into these two types has been recognized by researchers in other parts of the country (3,19,24,29).…”
mentioning
confidence: 98%
“…Planting seed lots with infection levels of more than 40% has been reported to cause significant yield losses (33). Infected seeds also may introduce the pathogen into new areas (15), and seed detection is important to avoid yield losses (9). Infected seeds also may introduce the pathogen into new areas (15), and seed detection is important to avoid yield losses (9).…”
mentioning
confidence: 99%